New American unilateralism - Đurković Miša (Međunarodni Problemi)
The article deals with the phenomenon of the so-called New American Unilateralism. The author searches for the causes, genesis and sources of such a behaviour of the current American administration, especially emphasising the importance of the neoconservative group, which has been creating, justifying and implementing this kind of unilateral strategy. Criticism of this politics is presented, coming from different directions. The author concludes that it is more the new discourse than the new politics, since the politics of George W. Bush does not substantially differ from the politics of previous American presidents. Having that in mind, it seems possible to predict that the strategy of the next president will probably go along the same lines and unilateralism will keep on being practiced as long as the world functions according to the unipolar model, with US as a global hegemon.